Vacancy defects in UV‐transparent HVPE‐AlN. Issue 3 (17th February 2014) - Kuittinen, Tanja; Tuomisto, Filip; Kumagai, Yoshinao; Nagashima, Toru; Kinoshita, Toru; Koukitu, Akinori; Collazo, Ramón; Sitar, Zlatko
Abstract: We used positron annihilation spectroscopy to study bulk AlN single crystals grown by physical vapor transport (PVT) and hydride vapor phase epitaxy (HVPE). Unlike in previous measurements in AlN, we see a clear Alvacancy related lifetime component already at room temperature in HVPE‐AlN. Overall, our results show the more UV‐transparent HVPE‐AlN to have higher concentration of Al‐vacancy related defects than PVT‐AlN, suggesting that Al‐vacancies are not the origin of UV absorption in AlN. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)